Integration policy towards the contemporary challenges of migration: an example of Frankfurt (Oder) - Jańczak, Barbara Alicja (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
One of the most important tasks ahead of contemporary Europe is the introduction of an effective integration policy towards the newly arrived immigrants. Germany is one of the main receiving countries of refugees up to now. The paper aims to analyze the emigrational policy towards the newly arrived migrants in Frankfurt (Oder).
Keywords: immigrants; integration; integration policy; language policy